Capitalist Convergence? European (dis?)Integration and the Post-crash Restructuring of French and European Capitalisms. Issue 1 (2nd January 2021) - Clift, Ben; McDaniel, Sean
ABSTRACT: This article critiques and builds upon first-wave (Höpner and Schäfer 2010. A new phase of European integration: organised capitalisms in post-Ricardian Europe. West European Politics, 33 (2), 344–368) and second-wave (Johnston and Regan 2018. Introduction: is the European Union capable of integrating diverse models of capitalism? New Political Economy, 23 (2), 145–159) European Integration and comparative capitalisms literatures which posit convergence towards a single model of capitalism or growth. It utilises the case study of France to explore the impact of European integration and disintegration on national models of capitalism in the post-crisis era. The article focuses on the impact of integrative and disintegrative dynamics on France's 'state-industry-finance nexus', putting forward three core claims. First, French capitalism is not accurately captured by the above frameworks and remains better characterised by the concept of post- dirigisme . Indeed, comparative capitalisms debates must move beyond a simple bifurcation of capitalist types. Second, European integrative pressures must be viewed as fragmented, differentiating, mediated by domestic state actors and producing capitalist variegation and hybridisation. Countering functionalist tendencies within this literature, it shows how different conceptions of state-market relations crucially mediate the relationship between national capitalisms and European integration. Finally, in the context of Brexit, the dynamics of European dis integration – an issue not discussed so far in these debates – is contributing to a variegated and multi-directional process of capitalist restructuring in post-crisis France.